2020
DOI: 10.1177/1077546319889859
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent fault diagnosis method of rolling bearings based on Welch power spectrum transformation with radial basis function neural network

Abstract: In the intelligent fault diagnosis of rolling bearings, the high recognition accuracy is hardly achieved when small training samples and strong noise happen. In this article, a novel fault diagnosis method is proposed, that is radial basis function neural network with power spectrum of Welch method. This fault diagnosis model adopts the way of end-to-end operating mode. It takes the original vibration signal (time-domain signal) as input, and Welch method transforms the data from time-domain signals to power s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Because of their powerful nonlinear fitting ability, RBF neural networks can map a wide range of nonlinear relationships. In contrast, most loss functions, especially in deep learning, are nonconvex, and multiple local minima can be found [ 19 ]. In addition to the function's nonconvex nature, the spatial symmetry of the neural network's weights can result in a large number of local minima, emphasizing the importance of a good optimization algorithm.…”
Section: A Study On Regional Gdp Forecasting Analysis Of Shandong Economy In China Based On Rbfnn-ga Algorithmmentioning
confidence: 99%
“…Because of their powerful nonlinear fitting ability, RBF neural networks can map a wide range of nonlinear relationships. In contrast, most loss functions, especially in deep learning, are nonconvex, and multiple local minima can be found [ 19 ]. In addition to the function's nonconvex nature, the spatial symmetry of the neural network's weights can result in a large number of local minima, emphasizing the importance of a good optimization algorithm.…”
Section: A Study On Regional Gdp Forecasting Analysis Of Shandong Economy In China Based On Rbfnn-ga Algorithmmentioning
confidence: 99%
“…Network architectures applied for fault diagnosis can be separated as follows: (a) static (i.e., feed-forward) network in which the inputs for each layer only rely on the outputs of the previous layer and (b) dynamic network in which the inputs to a specific layer depend on the outputs of the previous layer and the previous iterations of the network itself [97]. Most ANN approaches proposed to date have been based on static networks, including the multi-layer perceptron (MPL) [52,[104][105][106], radial basis function network (RBF) [97,107,108], and general regression neural network (GRNN) [25]. Several dynamic networks (e.g., recurrent neural network) have been developed for fault diagnosis.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Zhou et al [107] combined unscented Kalman filter and RBF to detect fault in the pumping unit. Jin et al [108] applied radial basis function neural network with power spectrum of Welch method to bearing fault diagnosis and further discussed the limit performance of the neural network. RNN outperforms MPL and RBF due to the ability to consider temporal dependencies via local or global feedback connections in the network.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…They accurately obtained the prior transmissibility functions and concluded that the proposed method performed more accurately and reliably than the conventional method. Previously, the Welch method has been used in many studies and demonstrated better results compared with nonparametric methods 75–78 . Therefore, in the current study, we applied the Welch method to detect the multipath spectrum of multiconstellation systems.…”
Section: Introductionmentioning
confidence: 99%